The Prevalence and Factors Associated With Anxiety-Like and Depression-Like Behaviors in Women With Polycystic Ovary Syndrome - Lin, Han; Liu, Mingxing; Zhong, Dongmei; Ng, Ernest Hung Yu; Liu, Jianping; Li, Juan; Shi, Yu; Zhang, Chunren; Wen, Xiaohui; Mai, Zhefen; Ou, Miaoxian; Ma, Hongxia (Frontiers in Psychiatry, 2021)
Increasing evidence shows that polycystic ovary syndrome (PCOS) patients are particularly vulnerable to anxiety/depression-like behaviors. This study sought to determine the prevalence of anxiety/depression-like behaviors among women with PCOS and to identify factors associated with these behaviors. This study was a secondary analysis of three studies performed on Chinese women who were aged 18 to 40 and diagnosed with PCOS according to the modified Rotterdam criteria. We obtained 802 useable responses for the self-rating anxiety scale and 798 responses for the self-rating depression scale. The prevalence of anxiety-like and depression-like behaviors among women with PCOS was 26.1% (209/802) and 52.0% (415/798), respectively. Anxiety-like behaviors were associated with age, body image-related factors (including body mass index and waist-to-hip ratio), and hyperandrogenism-related factors (including free androgen index and hirsutism). Depression-like behaviors were associated with age, body image-related factors, hyperandrogenism-related factors, and metabolic factors (including fasting insulin, fasting plasma glucose, and homeostatic model assessment of insulin resistance).